Seven new Longicorn (Coleoptera, Cerambycidae) species from Iran - Danilevsky, Mikhail (Zootaxa, 2018)
Cortodera hodeki sp. nov. close to C. kaphanica Danilevsky, 1985 is described from Ardabil province; C. takabensis sp. nov. close to С. neali Danilevsky, 2004, C. rubenyani sp. nov. and C. kareli sp. nov. both close to C. pseudomophlus Reitter, 1889 are described from Iranian Kurdistan; C. lowlakanensis sp. nov. close to C. takabensis sp. nov. is described from Iranian West Azerbaijan; Dorcadion (Cribridorcadion) rezai sp. nov., which belongs to D. laeve-group of species is described from Shiraz. Phytoecia (Pilemia) ghobarii sp. nov. very close to Turkish Ph. (P.) konyaensis Danilevsky, 2010 is described from Iranian Kurdistan. Distinguishing characters are discussed.